Challenges of land management in the agro sphere, caused by military aggression, and the ways of their solution - Dorosh, Y.; Barvinskyi, А.; Dorosh, O.; Svyrydova, L. (Land Management, Cadastre and Land Monitoring, 2023)
The current state of agricultural lands, especially those damaged as a result of emergency situations and hostilities, is analyzed. It has been proven that the algorithm for removing lands damaged as a result of military operations from agricultural circulation must be fixed at the legislative level by making appropriate amendments and additions to the Land Code of Ukraine, Laws of Ukraine: "On Land Protection", "On Land Management". The current Land Conservation Procedure should be supplemented with criteria and indicators for establishing the degree of mechanical destruction and/or chemical pollution, because the direction, content and volume of restoration works and, accordingly, the amount of their financing depend on this. It is emphasized that only a differentiated approach to the transformation of technogenically polluted lands allows rational spending of funds and achieving the maximum environmental protection effect.It is emphasized that in today's conditions, for an adequate and timely response to challenges in the field of land use and protection, in rural areas, land management should have a dynamic multivariate (alternative) nature, especially at the local level, based on the main legally established principles.The tasks of land management in the agrarian sphere, caused by military aggression, are formulated, and the ways of their solution are substantiated. The list of shortcomings in the legislative norms, which are present in the modern context when compiling land management documentation, is given.
Keywords: land management; agricultural land; destruction of soil cover; chemical pollution of land.